An overview of grid-connected fuel cell system for grid support. (November 2022) - Guo, Renqi; Li, Quan; Zhao, Nan
Abstract: Fuel cell (FC) technology has become popular recently for its low-carbon characteristics. Depending on the different structures of the system and controls of the converter, grid-connected FC systems can achieve various goals in supporting the grid. Grid-following (GFL) and grid-forming (GFM) control are normally used for the controller of converters. In this paper, an overview of how the grid-connected FC system can support the grid is presented. The basic grid-connected FC system operation principles are firstly introduced, followed by the comparisons between FC and batteries, which shows the advantages and disadvantages of the FC system. Different functions of the FC system are then reviewed. Renewable sources, particularly wind turbines and photovoltaic farms, have some problems in the integration with the grid during the insufficient wind speed or radians, and FC systems can help renewables achieve better integration with the grid. Moreover, FC cannot only balance the system power as a primary energy source, but provide voltage support during system contingencies as well. Nevertheless, the FC system has some problems with oscillation and harmonics. Finally, the challenges of grid-connected FC systems are presented.